2021
DOI: 10.1055/s-0041-1733316
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Awareness and Attitude towards Oral Precancer and Cancer among Narikuravar Population in Pondicherry State

Abstract: Objective Literature revealed that oral health status and awareness about oral hygiene measures of Narikuravar tribes were very poor. There was also an increased prevalence of tobacco usage among this population. Considering this, incidence and prevalence of oral precancerous and cancerous lesions are expected to be high in this population. Surprisingly, the literature search revealed a lack of data on the awareness, knowledge, and prevalence of oral cancer and precancer in this group. The primary objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Cigarette smoke weakens the immunity in the oral cavity by causing gingivitis, periodontitis, and oral cancer. In certain rural areas still, issues like poverty, illiteracy, poor health care, poor knowledge, and lack of awareness about oral health, oral hygiene, and the prevalence of oral cancer or lack of knowledge of oral cancer are prevalent [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoke weakens the immunity in the oral cavity by causing gingivitis, periodontitis, and oral cancer. In certain rural areas still, issues like poverty, illiteracy, poor health care, poor knowledge, and lack of awareness about oral health, oral hygiene, and the prevalence of oral cancer or lack of knowledge of oral cancer are prevalent [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a survey conducted in 2016 by Ahire[ 18 ] reported that the patients reported to their department their knowledge and awareness regarding oral premalignant lesions were found to be low. Muthanandam et al .,[ 25 ] 2021 conducted a questionnaire-based study on the Narikuravar population of Pondicherry to assess their knowledge and awareness about pre-cancer and cancer and found that almost 100% populations were unaware of its signs and symptoms and the consequences of precancerous lesions. Similar results were observed in a study conducted by Kadashetti et al .,[ 26 ] where the patients who visited to the hospital and participated in the survey were unaware of oral premalignant lesions and signs and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Regrettably, 40% of the study population had completed only up to primary school and only 6.4% had completed higher secondary school. Likewise, in a study conducted on Narikuravars of Pondicherry, 91% of the population was uneducated and only 8.3% had attended primary school [ 11 ]. This may be due to their nomadic lifestyle, where parents have turned to various jobs like selling beads, toys, and other items in markets, bus stands, fairs, and other places where their kids would never get the chance to attend school [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The government has, however, banned it following the implementation of the Wildlife Protection Act. They now have different jobs and live a nomadic lifestyle, selling beads, toys, and other items in markets, bus stands, and other public places [ 11 ]. Most members of this community lack the facility of housing and live on roadsides and in huts.…”
Section: Introductionmentioning
confidence: 99%